Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Mid-Chapter Check Point - Page 135: 19



Work Step by Step

$(f-g)(x)=f(x)-g(x)$ $(f-g)(x)=f(x)-g(x)=x^2-3x+8-(-2x-5)=x^2-x+13$ Plug in $x=5$ into $(f-g)(x)$: $(f-g)(5)=(5)^2-5+13=25-5+13=33$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.